Dothideomycete-plant interactions illuminated by genome sequencing and EST analysis of the wheat pathogen Stagonospora nodorum - Hane, J.; Lowe, R.; Solomon, P.; Tan, Kar-Chun; Schoch, C.; Spatafora, J.; Crous, P.; Kodira, C.; Birren, B.; Galagan, J.; Torriani, S.; McDonald, B.; et al. (2007)
Stagonospora nodorum is a major necrotrophic fungal pathogen of wheat (Triticum aestivum) and a member of the Dothideomycetes, a large fungal taxon that includes many important plant pathogens affecting all major crop plant families. Here, we report the acquisition and initial analysis of a draft genome sequence for this fungus. The assembly comprises 37,164,227 bp of nuclear DNA contained in 107 scaffolds. The circular mitochondrial genome comprises 49,761 bp encoding 46 genes, including four that are intron encoded. The nuclear genome assembly contains 26 classes of repetitive DNA, comprising 4.5% of the genome. Some of the repeats show evidence of repeat-induced point mutations consistent with a frequent sexual cycle. ESTs and gene prediction models support a minimum of 10,762 nuclear genes. Extensive orthology was found between the polyketide synthase family in S. nodorum and Cochliobolus heterostrophus, suggesting an ancient origin and conserved functions for these genes. A striking feature of the gene catalog was the large number of genes predicted to encode secreted proteins; the majority has no meaningful similarity to any other known genes. It is likely that genes for host-specific toxins, in addition to ToxA, will be found among this group. ESTs obtained from axenic mycelium grown on oleate (chosen to mimic early infection) and late-stage lesions sporulating on wheat leaves were obtained. Statistical analysis shows that transcripts encoding proteins involved in protein synthesis and in the production of extracellular proteases, cellulases, and xylanases predominate in the infection library. This suggests that the fungus is dependant on the degradation of wheat macromolecular constituents to provide the carbon skeletons and energy for the synthesis of proteins and other components destined for the developing pycnidiospores.